Graded therapeutic approach to fissure in ano: study of 50 cases - Vagholkar, Ketan (International Surgery Journal, 2019)
Background: Fissure in ano is one of the commonest disease affecting all age groups. The condition is quite painful leading to interference in activities of daily living. A wide variety of modalities ranging from medical to surgical approaches have been proposed. However no single modality can be called the gold standard of treatment. Hence the need to develop an optimum graded approach to manage the condition. Methods: Fifty consecutive cases of fissure in ano presenting in an acute state were studied prospectively to develop a therapeutic algorithm for rational treatment of the painful condition. Results: Conservative treatment was commenced in all cases. Eighteen required anal dilatation while out of these eighteen patients, ten required sphincterotomy despite anal dilatation. Four patients had recurrence of symptoms despite all surgical treatments. Conclusions: Conservative treatment still has a significant and positive outcome in fissure in ano. Anal dilatation and sphincterotomy are the next options of treatment. Therefore a graded multimodal approach is therapeutic in treating fissure in ano.